ANALISIS YANG MEMPENGARUHI ADAPTIVE SELLING CAPABILITY DAN DAMPAKNYA TERHADAP KINERJA PENJUALAN PADA PERUSAHAAN FARMASI DI KOTA SEMARANG - Hastuti, Yenny Widya (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2014)
The purpose of this research is to test the influences of individual orientation value and salesmancompetence on adaptive selling capability to increase sales performance. Using these variables,the usage of these variables are able to solve the arising problem within pharmacy industry atSemarang city.The samples size of this research is 100 salesman pharmacy industry at Semarang city.Using the Structural Equation Modeling (SEM). The results show that the individual orientationvalue and salesman competence on adaptive selling capability to increase sales performance.The effect of individual orientation value on adaptive selling capability are significant; Theeffect of salesman competence on adaptive selling capability are significant; The effect ofindividual orientation value on sales performance are significant; The effect of salesmancompetence on sales performance are significant; and The effect of adaptive selling capabilityon sales performance are significant;